Are accelerometers a valid tool for measuring overground sprinting symmetry? - Kenneally-Dabrowski, C. J. B.; Serpell, B. G.; Spratford, W. (International Journal of Sports Science & Coaching, 2018)
Running symmetry is important for performance, injury prevention or rehabilitation in many sports. However, current methods for measuring running symmetry are expensive, time consuming and must typically be constrained to a non-task representative laboratory setting. The aim of this study was to validate a method that used accelerometry data to determine running symmetry during maximal over ground sprinting for abled bodied athletes. Thirteen elite male athletes performed three 40 m maximal sprints on an indoor running track while data were collected from eight force plates and an accelerometer positioned between the scapulae against the spine. Correlations and Bland-Altman analyses were used to assess validity. Time spent either side of the vertical axis was compared to maximal medio-lateral force from either side of the body using a symmetry index approach. Results revealed only a trivial relationship (r = 0.088, p = 0.616) and poor agreement (bias = 0.189, p = 0.000). Likewise, stride time from the accelerometer and force plates exhibited a small relationship (rs = -0.177, p = 0.310) and significant bias (bias = -0.026, p = 0.000), yet showed smaller limits of agreement. It was concluded that both of the methods for measuring sprinting asymmetry using accelerometer data had poor internal validity. However, of these measures, stride time showed the best capacity to calculate running symmetry during maximal effort sprints. Overall, it is suggested that coaches exhibit caution when interpreting running symmetry measures from accelerometers, and also carefully consider where the accelerometer is placed on the body. ABSTRACT FROM AUTHOR